Zero echo time MRI improved detection of erosions and sclerosis in the sacroiliac joint in comparison with LAVA-flex - Lin, Churong; Liu, Dong; Wen, Huiquan; Liu, Budian; Tu, Liudan; Gu, Jieruo (Frontiers in Endocrinology, 2023)
Background: T1w spoiled 3D-GRE pulse sequences, exemplified by Liver Acquisition with Volume Acceleration-flexible MRI (LAVA-Flex), are currently the preferred MR sequence for detecting erosions of the sacroiliac joint (SIJ). However, zero echo time MRI (ZTE) is recently reported to provide excellent visualization of the cortical bone. Purpose: To directly compare the diagnostic accuracy of ZTE and LAVA-Flex in the detection of structural lesions of the SIJ, including erosions, sclerosis and joint space changes. Materials and methods: Two readers independently reviewed the ldCT, ZTE and LAVA-Flex images of 53 patients diagnosed as axSpA and scored the erosions, sclerosis and joint space changes. Sensitivity, specificity and Cohen’s kappa (κ) of ZTE and LAVA-Flex were calculated, while McNemar’s test was employed to compare the two sequences for the positivity of detecting the structural lesions. Results: Analysis of diagnostic accuracy showed a higher sensitivity of ZTE in comparison with LAVA-Flex in the depiction of erosions (92.5% vs 81.5%, p<0.001), especially first-degree erosions (p<0.001) and second-degree erosions (p<0.001), as well as sclerosis (90.6% vs 71.2%, p<0.001), but not joint space changes (95.2% vs 93.8%, p=0.332). Agreement with ldCT was also higher in ZTE in the detection of erosions than LAVA-Flex as indicated by the κ values (0.73 vs 0.47), as well as in the detection of sclerosis (0.92 vs 0.22). Conclusion: With ldCT as the reference standard, ZTE could improve diagnostic accuracy of erosions and sclerosis of the SIJ in patients suspected of axSpA, in comparison with LAVA-Flex.